Efektivitas Terapi Rendam Kaki Air Hangat untuk Menurunkan Tekanan Darah pada Penderita Hipertensi - Alfath Dzea Haqilana; M. Aqil Argyanto; Satriya Pranata (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
Background: Hypertension has become a serious global health issue, with the number of sufferers increasing from 650 million in 1990 to 1.4 billion in 2024. In Indonesia, the prevalence reached 34.1% in 2018, with a higher proportion among women at 36.85%. While pharmacological treatments are available, they often face constraints regarding costs and side effects. Hydrotherapy, specifically warm water foot soaks, serves as a safe and accessible non-pharmacological alternative to lower blood pressure naturally. Objective: This study aims to evaluate the effectiveness of warm water foot soak therapy in reducing blood pressure among hypertension patients. Methods: This study utilized a literature review design by accessing national and international journal databases, including Garuda, ProQuest, and PubMed. The search strategy employed keywords such as